1070 Outcomes for babies with prolonged neonatal stays requiring ongoing respiratory care in a UK tertiary neonatal and respiratory centre. (17th August 2022) - Edwards, Chris; Fraser, Caroline; Gopalakaje, Saikiran; Johnson, Kathryn
Abstract : Aims: Leeds Childrens' Hospital neonatal unit is a busy tertiary care centre admitted approximately 10, 000 sick and pre-term infants a year. A number of these infants require ongoing respiratory support and are transferred to the respiratory ward for ongoing care. Our aims were to To review the outcomes for these babies to provide realistic information to parents Identify any risk factors for prolonged stay or poor outcome Methods: Babies born between February 2012 and February 2019 who were transferred from NICU to care under the respiratory team had a notes review. BadgerNet, the UK national neonatal database, and PPM+ the electronic patient records system used at Leeds Teaching Hospitals, were used to research patient information. Data collected was entered in to a spreadsheet and collated. Results: Of a total of 42 babies we had full data for 28 and partial data for 1. The gestational age range at birth was 24+1 to 39+1 weeks. Average gestational age of 29 weeks and 5 days. Average time on a ventilator was 40 days (range 0-109 days). Average length of stay on NNU 128 days. Average length of stay on the respiratory ward was 89 days. Fourteen arrived on the ward on high flow support. Twenty babies had a gastrostomy. Three of the 28 babies died before discharge home. Overall mortality from birth until completion of data collection was 25%. Four went home without any respiratory support, 13 went home in low flow oxygen, 3 with non-invasive ventilation, 3 with humidified or high flow oxygen. One had a tracheostomy. Data wasn't available for the last patient. Conclusion: If discharged to the respiratory ward, the length of stay is likely to be considerable and there is a significant mortality in this group. The most common operation for these children is a gastrostomy. This was for aiding long term feeding and to help manage gastro-oesophageal reflux. Most children who are admitted on high flow oxygen can be weaned to low flow oxygen in under 3 months. Although no specific risk factors were identified, it was recognised that the average length of time spent ventilated in NICU was greater than for babies who were not admitted to the respiratory ward. These figures are helpful information for parents of these babies. They have formed the basis of MDT work between neonatologists and respiratory physicians to improve inpatient management